Interfaces university - society in the transdisciplinary prospective: Social Communication and Institutional-web Discourse associated with the organization of knowledge in Universities in Chile (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The following investigation had as an objective to analyse the usages of the Institutional Discourse (ID) from Chilean universities self-described as complex, in relation to the Knowledge Organization (KO) and relevant inter-disciplinaries initiatives that are informed at the level of static structures and pieces of news published on each official website. In this context, and, through a Critical Discourse Analysis (CDA), the communicative strategies deployment is explored, as well as the production and broadcasting of their institutional discourse. Likewise, their exposure and disposal on web pages. On this basis, the qualitative information is contributed to the discussion around the formats and social communication devices, referred to the concepts of inter and trans-disciplines in the context of higher education in the nation. The results, reflect the emergency, centrality and communicational value of the inter and trans-disciplinary prospective in the Chilean university context. However, the epistemological and methodological conditions are evidenced for its organizational, critical, and sustainable deployment
Keywords: Tertiary education; knowledge organization (KO); institutional discourse (ID); critical discourse analysis (CDA)